2022
DOI: 10.2174/1574888x16666210622123942
|View full text |Cite
|
Sign up to set email alerts
|

Development and Clinical Application of Tumor-derived Exosomes in Patients with Cancer

Abstract: : A tumor is an abnormal growth of cells within a tissue that can lead to death due to late diagnosis, poor prognosis, drug resistance, and finally enhanced metastasis formation. Exosomes are nanovesicles that have been derived from all the different cell types. These vesicles can transfer various molecules, including the distinct form of nucleic acids (mRNA, miRNA, and circRNA) and proteins. Tumor-derived exosomes (TEXs) have exceptionally important roles through multiple molecular and cellular pathways like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…In addition to the nucleotides, TEX have been increasingly recognized as key players in cancer that are able to modulate immune cells. As previously described, TEX have shown dual effects in the TME [41,[77][78][79]. TEX were reported to elicit immunostimulatory as well as immunosuppressive effects, translating into anti-and pro-tumorigenic effects [41,[80][81][82].…”
Section: Discussionmentioning
confidence: 73%
“…In addition to the nucleotides, TEX have been increasingly recognized as key players in cancer that are able to modulate immune cells. As previously described, TEX have shown dual effects in the TME [41,[77][78][79]. TEX were reported to elicit immunostimulatory as well as immunosuppressive effects, translating into anti-and pro-tumorigenic effects [41,[80][81][82].…”
Section: Discussionmentioning
confidence: 73%
“… 58 In addition, exosomal circRNA carries the biological information related to the primary tumor, easily crosses various biological barriers, and exists in a large number of body fluids from different sources, which brings great hope for the diagnosis and treatment of osteosarcoma and can be used as a biomarker for early diagnosis and prognosis evaluation. 59 The isolation and detection of circRNA from tumor-associated exosomes need cutting-edge technology, so it is necessary to develop more accurate and straightforward detection methods to monitor and find new therapeutic targets.…”
Section: Application Of Circrna In the Diagnosis And Treatment Of Ost...mentioning
confidence: 99%
“…Abundant evidence has shown that cells from individuals with diseases and healthy subjects secreted exosomes containing different proteins and RNAs into the circulation and body fluid, which makes exosomes applicable for liquid biopsy as potential diagnostic biomarkers. 119 , 120 Melo and coworkers found that exosomal proteoglycan glypican‐1 (GP1) was specifically present in the serum of patients with pancreatic cancer with high sensitivity and exosomal GP1 level is highly positively correlated with the tumor burden. Correspondingly, exosomal GP1 level is also correlated with survival of pre‐ and post‐surgical patients, indicating exosomal GP1 ideal to serve as diagnostic and prognostic biomarkers for pancreatic cancer.…”
Section: Exosomes As Disease Biomarkersmentioning
confidence: 99%